Cosmetological applications of Citrus limon: A mini-review - Ee Jie Leong; Lee Fang Tan
Citrus limon has gained attention in cosmetology for its diverse bioactive compounds. This review explores its cosmetological applications, emphasising antioxidant, anti-inflammatory, antimicrobial, skin-brightening, preservative, and substance-penetrating properties. The genus Citrus is briefly described, followed by details on C. limon's botanical features, distribution, phytochemical composition, and biological activities. Lem1, a natural compound from C. limon, exhibits strong antioxidant activity, making it a potential ingredient for natural anti-ageing skincare. C. limon's potent antimicrobial properties make it effective against various bacteria, addressing skin issues like acne and serving as a natural preservative in cosmetics. Rich in limonene and vitamin C, C. limon inhibits tyrosinase activity and reduces melanin formation, showing promise in cosmetics for controlling skin pigmentation and promoting even-toned, brighter skin. Safety considerations in cosmetic use are also addressed. Overall, C. limon is a valuable natural ingredient, enhancing efficacy and safety in cosmetic products.